False‐positive finding of retropharyngeal lymph node recurrence in both fluorine 18FDG PET and MRI in a patient with nasopharyngeal carcinoma. Issue 4 (28th August 2015) - Tsai, Ming‐Chen; Shu, Yu‐Chi; Hsu, Chia‐Chen; Lin, Chih‐Kung; Lee, Jih‐Chin; Chu, Yueng‐Hsiang; Huang, Wen‐Yen
Abstract: Background: Biopsy of the retropharyngeal node is not routinely accessible. The diagnosis of retropharyngeal lymph node recurrence in patients with nasopharyngeal carcinoma (NPC) is often based on an imaging study. Methods: We reported a patient with NPC who was incorrectly diagnosed with left retropharyngeal lymph node recurrence by both MRI and positron emission tomography (PET)/CT. Results: A woman who was treated for stage IVA NPC 2 years previously was found to have a nodal lesion in the left retropharyngeal space on MRI together with focal fluorodeoxyglucose (FDG) uptake on PET/CT. Locoregional recurrence was suspected, and surgery was performed. Subsequent pathology results showed reactive lymphoid hyperplasia. Conclusion: Although tissue biopsy for the retropharyngeal node is technically difficult, this case demonstrates that tumor recurrence cannot be diagnosed even based on both positive findings on MRI and PET/CT in patients with NPC. © 2015 Wiley Periodicals, Inc. Head Neck 38: E84–E86, 2016